The Application of UN Charter Chapter XI to Military Occupations - Attenhofer, Jonas (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2022)
This book argues that Chapter XI of the UN Charter should be applied to military occupations. The book operates in two parts. First, it describes the status quo of the law of military occupation and the economic incentive that this status quo holds for the occupant. Second, it shows by way of a contemporary interpretation, how Chapter XI should be applied and what it would mean for the economic rights of the inhabitants. It will be argued that the application of Chapter XI would make it economically unattractive for an occupant to stay in the foreign territory, while leaving his right to self-defense intact. This book is of interest to scholars and practitioners who are seeking new avenues for the laws of military occupation.